Disc flaring with TNG50: diversity across Milky Way and M31 analogues - Sotillo-Ramos, Diego; Donnari, Martina; Pillepich, Annalisa; Frankel, Neige; Nelson, Dylan; Springel, Volker; Hernquist, Lars (Monthly notices of the Royal Astronomical Society, 2023)
We use the sample of 198 Milky Way (MW) and Andromeda (M31) analogues from TNG50 to quantify the level of disc flaring predicted by a modern, high-resolution cosmological hydrodynamical simulation. Disc flaring refers to the increase of vertical stellar disc height with galactocentric distance. The TNG50 galaxies are selected to have stellar discy morphology, a stellar mass in the range of M* = 1010.5-11.2 M⊙, and an MW-like Mpc-scale environment at z = 0. The stellar discs of such TNG50 MW/M31 analogues exhibit a wide diversity of structural properties, including a number of galaxies with disc scale length and thin and thick disc scale heights that are comparable to those measured or inferred for the Galaxy and Andromeda. With one set of physical ingredients, TNG50 returns a large variety of flaring flavours and amounts, also for mono-age stellar populations. With this paper, we hence propose a non-parametric characterization of flaring. The typical MW/M31 analogues exhibit disc scale heights that are 1.5-2 times larger in the outer than in the inner regions of the disc for both old and young stellar populations, but with a large galaxy-to-galaxy variation. Which stellar population flares more, and by how much, also varies from galaxy to galaxy. TNG50 de facto brackets existing observational constraints for the Galaxy and all previous numerical findings. A link between the amount of flaring and the z = 0 global galaxy structural properties or merger history is complex. However, a connection between the scale heights and the local stellar vertical kinematics and gravitational potential is clearly in place.
Veröffentlicht: 23. Mai 2023
Gesehen am 22.08.2023